ANALYSIS OF MATHEMATICAL MODELS OF MULTI-FREQUENCYPIONEERING AUTOMOTIVE SYSTEMS - STETSIUK, Viktor; HORIASCHENKO, Kostyantyn (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the work the analysis of mathematical models of multi-frequency piezoresonance oscillatory systems is carried out. It is indicated on the essence of the phenomenon of multifrequency excitation, as a normal physical property of quartz resonators. However, for the tasks of constructing highly stable self-oscillating systems as a source of reference oscillation, this property of the CR is undesirable, moreover, it is struggling with all possible methods. As a result of the analysis of mathematical models of multifrequency oscillation systems, it is established that none of them allows to fully study the dynamics of multifrequency oscillation systems under conditions of vibrational destabilizing effects, which requires their further study. Proposed own approach to solving problems of simulation of multi-frequency PCBs.
Keywords: quartz resonator; piezoresonance system; oscillations; multifrequency; mathematical model